Panfungal Polymerase Chain Reaction for Identification of Fungal Pathogens in Formalin-Fixed Animal Tissues. (July 2017) - Meason-Smith, Courtney; Edwards, Erin E.; Older, Caitlin E.; Branco, Mackenzie; Bryan, Laura K.; Lawhon, Sara D.; Suchodolski, Jan S.; Gomez, Gabriel; Mansell, Joanne; Hoffmann, Aline Rodrigues
Identification of fungal organisms often poses a problem for pathologists because the histomorphology of some fungal organisms is not specific, fresh tissues may not be available, and isolation and identification in culture may take a long time. The purpose of this study was to validate the use of panfungal polymerase chain reaction (PCR) to identify fungal organisms from formalin-fixed paraffin-embedded (FFPE) tissues. Formalin-fixed paraffin-embedded curls were tested from 128 blocks containing canine, feline, equine, and bovine tissues with cutaneous, nasal, pulmonary, and systemic fungal infections, identified by the presence of fungi in histologic sections. Quantitative scoring of histologic sections identified rare (11.9%), occasional (17.5%), moderate (17.5%), or abundant (53.1%) fungal organisms. DNA was isolated from FFPE tissues and PCR was performed targeting the internal transcribed spacer 2 (ITS-2) region, a segment of noncoding DNA found in all eukaryotes. Polymerase chain reaction products were sequenced and identified at ≥97% identity match using the Basic Local Alignment Search Tool and the NCBI database of ITS sequences. Of the 128 blocks, 117 (91.4%) yielded PCR products and high-quality sequences were derived from 89 (69.5%). Sequence and histologic identifications matched in 79 blocks (61.7%). This assay was capable of providing genus- and species-level identification when histopathology could not and, thus, is a beneficial complementary tool for diagnosis of fungal diseases.